West Europe Report No 2011 - JOINT PUBLICATIONS RESEARCH SERVICE ARLINGTON VA (1982)
This report contains information concerning Western Europe. The following topics and countries are included: (1) energy economics; Sweden, (2) economic; Austria, Belgium, Denmark, France, Norway, Turkey, (3) political; Denmark, Federal Republic of Germany, Finland, Iceland, Sweden, (4) military; Denmark, Federal Republic of Germany, and (5) international affairs.